Investigation on the presence of Sunset Yellow and Tartrazine in commercial beverages and quantitation using Ion-Pair formation and extraction / Zailuddin Ariffin, Faridah Hanum Badrun and Baharudin Salleh - Ariffin, Zailuddin; Badrun, Faridah Hanum; Salleh, Baharudin (2682-9223, 2010)
In this work, 18 different commercial beverages were analyzed for the detection of Sunset Yellow and Tartrazine by paper chromatography. Quantitation of samples containing only one added colour proceeded using the ion pair formation and extraction method. The results obtained showed that all the commercial beverages tested contain synthetic colours permitted for use based on the Malaysian Food Act 1983. Quantitation of soft drinks which contained only one added colour complied with the U.K. standard, although one sample showed a slight excess compared to the set limit of 50 mg/L.